On grand strategy - Gaddis, John Lewis (New york Penguin Press, 2018)
John Lewis Gaddis, the distinguished historian of the Cold War, has for almost two decades co-taught grand strategy at Yale University with his colleagues Charles Hill and Paul Kennedy. Now, in On Grand Strategy, Gaddis reflects on what he has learned. In chapters extending from the ancient world through World War II, Gaddis assesses grand strategic theory and practice in Herodotus, Thucydides, Sun Tzu, Octavian/Augustus, St. Augustine, Machiavelli, Elizabeth I, Philip II, the American Founding Fathers, Clausewitz, Tolstoy, Lincoln, Wilson, Franklin D. Roosevelt, and Isaiah Berlin. On Grand Strategy applies the sharp insights and wit readers have come to expect from Gaddis to times, places, and people he$1 (Bs never written about before. For anyone interested in the art of leadership, On Grand Strategy is, in every way, a master class.s
Keywords: Military art and science; Strategic culture; Strategic planning